2011
DOI: 10.1111/j.1754-4505.2011.00185.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental treatment needs in Dutch nursing homes offering integrated dental care

Abstract: The purpose of this study was to determine the dental treatment needs of the residents in nursing homes (NHs) where integrated dental care has been offered without financial barriers. The dental status and surgical, prosthetic, restorative, and periodontal treatment needs were determined for 432 residents (average age 78.8 years) in three Dutch NHs. Although the subjects had no complaints, 72% had dental treatment needs. It was determined that treatment was necessary for 64% of the edentulous subjects (N = 316… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 15 publications
0
24
0
3
Order By: Relevance
“…Al meer dan 35 jaar vinden onderzoekers een discrepantie tussen klinische (door de tandarts vastgestelde) behandelnoodzaak en subjectieve (door de patiënt ervaren) behandelnoodzaak en tussen subjectieve behandelnoodzaak en tandartsbezoek (Grabowski en Bertram, 1975;Gerritsen et al, 2011). Van de 100 ouderen bij wie een klinische behandelnoodzaak is vastgesteld, ervaart minder dan de helft de noodzaak voor behandeling, en slechts ruwweg een kwart neemt daadwerkelijk initiatief om een tandarts te bezoeken (Ferro et al, 2008;Gerritsen et al, 2011).…”
Section: Inleidingunclassified
See 2 more Smart Citations
“…Al meer dan 35 jaar vinden onderzoekers een discrepantie tussen klinische (door de tandarts vastgestelde) behandelnoodzaak en subjectieve (door de patiënt ervaren) behandelnoodzaak en tussen subjectieve behandelnoodzaak en tandartsbezoek (Grabowski en Bertram, 1975;Gerritsen et al, 2011). Van de 100 ouderen bij wie een klinische behandelnoodzaak is vastgesteld, ervaart minder dan de helft de noodzaak voor behandeling, en slechts ruwweg een kwart neemt daadwerkelijk initiatief om een tandarts te bezoeken (Ferro et al, 2008;Gerritsen et al, 2011).…”
Section: Inleidingunclassified
“…Van de 100 ouderen bij wie een klinische behandelnoodzaak is vastgesteld, ervaart minder dan de helft de noodzaak voor behandeling, en slechts ruwweg een kwart neemt daadwerkelijk initiatief om een tandarts te bezoeken (Ferro et al, 2008;Gerritsen et al, 2011).…”
Section: Inleidingunclassified
See 1 more Smart Citation
“…Studies have indicated that, of a group of non-institutionalized elderly people with clinically assessed or normative oral treatment needs, about half perceived the need and about one quarter sought treatment [4,7]. Recent studies among elderly residents in Dutch and Italian nursing homes showed even larger differences between normative and self-perceived needs [8,9]. Apparently, large discrepancies exist between self-perceived and normative treatment need, and between self-perceived treatment need and service-use.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] The UK decennial Adult Dental Health Surveys (ADHSs) commencing in 1968 through to 2009 have reported increasing numbers of older people retaining some natural teeth, even though they are often heavily restored. [6][7][8][9][10] Unfortunately, access to dental care for care home residents is not always straightforward.…”
Section: Introductionmentioning
confidence: 99%